The Effects of the Affordable Care Act on Workplace Absenteeism of Overweight and Obese Workers - Ethan Grumstrup; Md. Mobarak Hossain; Sankar Mukhopadhyay; Olga Shapoval (Institute of Labor Economics (IZA), 2019)
In this paper, we examine whether the expansion of health insurance coverage brought on by the Patient Protection and Affordable Care Act of 2010 (ACA), led to a decline in absenteeism among overweight and obese individuals. We use data from the National Health Insurance Survey (NHIS) to compare absenteeism among overweight and obese workers to absenteeism among normal-weight workers before and after the ACA. Our results suggest that in the post-ACA period, the probability of being absent declined by about 1.3 (1.5) percentage points among obese (overweight) individuals. Disaggregated regressions suggest that the effect is significant among women, but not among men. Furthermore, our estimates (using a Tobit model) indicate that the obese (overweight) workers missed 0.33 (0.46) fewer days after the ACA. Again, the effect is concentrated among women. Our results show that improved health outcomes led to reduced absenteeism. Our results also show that there are no decline in absenteeism among elderly (age>=65) adults (who did not experience any increase in health insurance coverage as a result of the ACA), suggesting that the decline in absenteeism is indeed due to the expansion of health insurance coverage due to the ACA. Our estimates imply that the ACA reduced the cost associated with absenteeism by about 350 million per year.
Keywords: I13; I18; J08; 330; Affordable Care Act; obesity; overweight; absenteeism